Characterization of evolutionarily distinct rice BAHD‐Acyltransferases provides insight into their plausible role in rice susceptibility to Rhizoctonia solani. Issue 3 (9th September 2021) - Kumar, Gulshan; Kumar, Pankaj; Kapoor, Ritu; Lore, Jagjeet Singh; Bhatia, Dharminder; Kumar, Arun
Abstract: Plants produce diverse secondary metabolites in response to different environmental cues including pathogens. The modification of secondary metabolites, including acylation, modulates their biological activity, stability, transport, and localization. A plant‐specific BAHD‐acyltransferase ( BAHD‐AT ) gene family members catalyze the acylation of secondary metabolites. Here we characterized the rice ( Oryza sativa L.) BAHD‐ATs at the genome‐wide level and endeavor to define their plausible role in the tolerance against Rhizoctonia solani AG1‐IA. We identified a total of 85 rice OsBAHD‐AT genes and classified them into five canonical clades based on their phylogenetic relationship with characterized BAHD‐ATs from other plant species. The time‐course RNA sequencing (RNA‐seq) analysis of OsBAHD‐AT genes and qualitative real‐time polymerase chain reaction (qRT‐PCR) validation showed higher expression in sheath blight susceptible rice genotype. Furthermore, the DNA methylation analysis revealed higher hypomethylation of OsBAHD‐AT genes that corresponds to their higher expression in susceptible rice genotype, indicating epigenetic regulation of OsBAHD‐AT genes in response to R. solani AG1‐IA inoculation. The results shown here indicate that BAHD‐ATs may have a negative role in rice tolerance against R. solani AG1‐IA possibly mediated through the brassinosteroid (BR) signaling pathway. Altogether, the present analysis suggests the putative functions of several OsBAHD‐AT genes, which will provide a blueprint for their functional characterization and to understand the rice– R. solani AG1‐IA interaction. Core Ideas: OsBAHD‐AT genes involved in acylation of secondary metabolites identified in the rice genome. OsBAHD‐AT genes were differentially expressed in response to R. solani AG1‐IA infection. Higher expression of OsBAHD‐AT genes in susceptible genotype suggested role in susceptibility. The epigenetic regulation via cytosine DNA methylation of OsBAHD‐AT genes was revealed.